2016
DOI: 10.2527/jas.2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mature body weight and stocking rate on cow and calf performance, cow herd efficiency, and economics in the southeastern United States1

Abstract: Eight 4-ha mixed warm-season grass pastures in southwestern Arkansas (33°40'4″ N, 93°35'24″ W, and elevation 107 m) were stocked with either large mature size (571 kg [SD 55.2] BW) or small mature size (463 kg [SD 58.2] BW) spring-calving cows at 4 stocking rates (SR; 1, 1.5, 2, or 2.5 cow-calf pairs/ha) over 4 yr to test the effects of SR and mature body size on cow and calf performance and system economics. Each pasture received 112 kg/ha N as ammonium nitrate in May and was broadcast seeded to annual ryegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
4
13
1
Order By: Relevance
“…Net return per hectare of HR ($1,025 ± 63.0/ha) was greater (P < 0.01) than that of MR ($479 ± 63.0/ha), which was numerically greater than that of CG ($429 ± 63.0/ha). The relationship between costs on a per-hectare and per-cow basis to the increased SR of HR in the current experiment are similar to those reported by Beck et al (2016), who reported that as SR increased, total cost per hectare increased but total cost per cow decreased. Beck et al (2016) likewise found that as SR increased, net return per hectare increased, but in contrast to the current research, net return per cow also increased with increasing SR. Wyatt et al (2013a) found that labor costs per cow decreased with increasing SR, along with increasing total sales revenue and return over total expenses.…”
Section: Economicssupporting
confidence: 89%
See 3 more Smart Citations
“…Net return per hectare of HR ($1,025 ± 63.0/ha) was greater (P < 0.01) than that of MR ($479 ± 63.0/ha), which was numerically greater than that of CG ($429 ± 63.0/ha). The relationship between costs on a per-hectare and per-cow basis to the increased SR of HR in the current experiment are similar to those reported by Beck et al (2016), who reported that as SR increased, total cost per hectare increased but total cost per cow decreased. Beck et al (2016) likewise found that as SR increased, net return per hectare increased, but in contrast to the current research, net return per cow also increased with increasing SR. Wyatt et al (2013a) found that labor costs per cow decreased with increasing SR, along with increasing total sales revenue and return over total expenses.…”
Section: Economicssupporting
confidence: 89%
“…Cow BCS were above the BCS that would impact reproductive performance of the cows (Selk et al, 1988), and therefore, cow BCS was not likely a factor in reproductive success among pasture management system. Similar to the current research, Beck et al (2016) reported that pregnancy rates were not affected by increasing SR of cows from 1 to 2.5 cows/ha even though BCS were reduced by 0.36 units for each 1 cow/ha increase in SR.…”
Section: Cow and Calf Performancesupporting
confidence: 87%
See 2 more Smart Citations
“…For example, a recent study on fertilized small pastures (~8 ac) in southwestern Arkansas showed larger cows (1,258 lb) did wean~45 lb heavier calves than small cows (1,020 lb). 15 Contradictory results from a semi-arid rangeland environment in Wyoming recently indicated however that smaller cows weaned calves as heavy as the largest cows and may have an advantage over large cows due to their ability to reduce forage inputs while simultaneously increasing total output measured in annual total weaned weight of calves. 16 Using this general result for the cow size*rangeland environment interaction, we developed a hypothetical modeling scenario presented in Table 1 that we suggest for western rangelands.…”
Section: Contemporary Drought Mitigation Strategies Using Livestock Gmentioning
confidence: 99%